CONTENTIOUS POLITICS: STRATEGI INTERNAL DAN EKSTERNAL MOBILISASI GERAKAN SOSIAL DALAM KOALISI - Khalis Asyifani (UNIVERSITAS SEBELAS MARET (UNS), 2024)
Social movements are one of the civil society entities that play an essential role in triggering elite responses to fulfill their responsibilities for the welfare of citizens. We can call various collective activism carried out by these social movements as a contention. This research analyzes internal and external strategies in the dynamics of movement mobilization by the Koalisi Serius Revisi UU ITE, which can create contentious political episodes. Several previous researches in Indonesia have outlined the internal and external strategies that influence the success of a single movement. However, no one explained that movement collaboration is vital in creating sustainable conflict. This research uses a qualitative method with a case study approach. This research chose five key informants by purposive sampling and did in-depth interviews, and supplemented with secondary data by documents and literature. The data obtained was elaborated using Sidney Tarrow's contentious politics perspective and resources mobilization by Edward, McCarthy, and Mataic. The first research finding is related to the importance of internal strategies with resource expansion, and external strategies with the management of threats and opportunities in the process of mobilizing social movements. The second finding shows that collaboration in social movement networks can strengthen the quality of collective contention and encourage the formation of contentious, sustainable political episodes.